Sustaining independent journals - CLARK, Timothy Adrian Robert (Institutional Knowledge at Singapore Management University, 2008)
Journals are a key conduit through which knowledge and ideas are certified and disseminated to the broad academy. In the last 20 years or so there have been dramatic changes in the journals market. The merging of publishers has resulted in considerable consolidation and increased levels of concentration. Library expenditure on serials has increased at the expense of books. The Association of Research Libraries (2006) reported that between 1986 and 2005 the unit cost of a journal subscription increased by 5.3 percent a year, whereas that for monographs grew by 3.2 percent. In the same period expenditures on serials increased by 7.6 percent, more than three times that for monographs (2.5 percent). Site licensing and the development of the Internet has had a substantial impact on the way in which academic information is distributed and provided a platform for greater access to journal content and facilitated the establishment of new online journals with open access. There are currently over 2,500 journals listed in the Directory of Open Access Journals (DOAJ) with 33 in management. However, the mortality rate amongst the journals is high. Morris (2006), for example, finds that by end of 2005, 9.7 percent of the 1213 journals in the DOAJ for which information could be traced had not published anything since at least 2003 and appeared to have ceased publication altogether. Given this situation, in this chapter we examine the particular issues editors face when developing and sustaining a distinctive independent journal. We are two of the General Editors of an independent (i.e., nonaffiliated to a professional association) journal — Journal of Management Studies (UMS) — that has managed to survive and prosper since 1964. Our purpose is to build on our experience of managing this journal and to provide insights for other editors of such journals; although many of the issues we raise have implications for editors of journals more generally.